(Evaluation of Retention of Metal Post and Core Fabricated by Conventional Technique and 3D Printing System (A Comparative In-Vitro Stud (Journal of Hama University, 2024)
Evaluation of Retention of Metal Posts and Cores Fabricated by Conventional Technique and 3D Printing System.Twenty mandibular orthodontic extractions premolars were endodontically treated. All teeth were cut 2 mm above cement-enamel junction. The root canals were enlarged to the same length and width using Gates-Glidn drills and Pesso reamers. Ferrule were made with 1mm finish line. The specimens were divided randomly into two groups according to the fabrication technique: Group A (1-10): samples were restored with a metal post and core fabricated using conventional technique. Group B (1-10): samples were restored with a metal post and core fabricated using 3D printing technique. All metal posts and cores were cemented by zinc phosphate cement. All specimens were subjected to tensile test in a universal testing machine at a crosshead speed of 0.5 mm/min. The mean of failure strength for all groups were calculated. The data were analyzed by Independent Samples T Test.There were statistically significant differences between the two groups in the research sample on confidence level 95%. The mean of failure strength in the first group 161,36 N (Conventional Technique) larger than the second group 118,52 N (3D printing Technique).Conclusion: Within the limits of this study, the metal posts and cores fabricated by the conventional technique revealed more retention than the metal posts and cores fabricated by the 3D printing technique.
Keywords: post and core; retention